(untitled) (Global Journal of Management and Business Research, 2018)
Job stress continues to be a concern and research interest across occupations and professions. However, to date most studies have addressed the employees working in the corporate sector. There are some studies which have tried to explore the determinants of job stress and its coping mechanisms among educators. The analysis in the study based on a sample of 188 private college educators attempts to understand the differences in the level of stress and coping mechanisms taking into account various demographic factors such as age, gender, education, marital status. The analysis reveals that female educators undergo more stress than males and their coping mechanisms differ significantly with regards to age and marital status.